Структурнi функцiї багатобозонної системи iз врахуванням прямих три- та чотиричастинкових кореляцiй - Vakarchuk, I. O.; Hryhorchak, O. I. (Publishing house "Academperiodika", 2019)
On the basis of the expression for the density matrix of interacting Bose particles in the coordinate representation with regard for the direct three- and four-particle correlations [I.O. Vakarchuk and O.I. Hryhorchak, J. Phys. Stud. 3, 3005 (2009)], the two-, three-, and four-particle structure factors of liquid 4He in a wide temperature interval were calculated in the approximation “one sum over the wave vector”. In the low-temperature limit, the expression obtained for the two-particle structure factor transforms into the well-known one. In the high-temperature limit, the expressions for the two-, three-, and four-particle structure factors are reduced to those for the ideal Bose gas. The results obtained can be applied to calculations of the thermodynamic functions of liquid 4He and to the determination of the temperature dependence of the first-sound velocity in a many-boson system.